Sensemaking of Shared Information: Perspective of Relevance in WhatsApp - Adjei, Joseph Kwame; Tweneboah, Pearl; Tobbin, Peter Ebo (Nordic and Baltic Journal of Information & Communications Technologies, 2020)
Despite the growing literature on information sharing in Social Media there is minimal understanding of how user’s estimate relevant information from shared information in the media. This paper explores the issue of relevant information sharing in social media by using a qualitative approach drawing on Media Richness Theory (MRT) through the lens of sensemaking to collect data. A questionnaire and interview were used to obtain data from regular users of WhatsApp with different backgrounds in the social network group context. Besides the capabilities of the media the results showed additional variables Channel Influence, Social influence, Nature of the Content, Experiential influence and Individual processing capabilities by conveyance and convergence play an important role in sensemaking for the shaping of relevant information. A framework for sensemaking of media relevant information is developed; the paper extends the Media Richness concept and has also opened a new area of research for innovative knowledge to emerge to address the challenges in social media information use which is highly relevant to IS research.